2016
DOI: 10.1016/j.medici.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and mean platelet volume/platelet count ratio in risk stratification of pulmonary embolism

Abstract: MPV and MPV/P were found to be associated with RV dysfunction and clinical severity in acute PE. Low MPV and MPV/P levels may be an indicator of low risk and, high WBC levels may be an indicator of high risk in patients with acute PE. RDW levels may not reflect severity of acute PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
3
16
1
Order By: Relevance
“…Most reports have shown that reduced MPV and/or MPV/P were linked to unsatisfactory prognosis in several carcinomas. 20,21 However, in advanced NSCLC studied by Omar et al, 22 they found elevated MPV and MPV/P could be an indicator of poor prognosis regarding OS, which is consistent with our current study. We conclude that this disparity maybe due to differing choice in cut-off points and in the type of carcinomas studied.…”
Section: Ta B L E 2 (Continued)supporting
confidence: 92%
“…Most reports have shown that reduced MPV and/or MPV/P were linked to unsatisfactory prognosis in several carcinomas. 20,21 However, in advanced NSCLC studied by Omar et al, 22 they found elevated MPV and MPV/P could be an indicator of poor prognosis regarding OS, which is consistent with our current study. We conclude that this disparity maybe due to differing choice in cut-off points and in the type of carcinomas studied.…”
Section: Ta B L E 2 (Continued)supporting
confidence: 92%
“…20 Several studies suggested its correlation with right ventricular (RV) dimensions and the severity of RV dysfunction. 15,21,22 Nevertheless, these studies were not consistent so far and some studies failed to find a correlation between MPV and disease severity. 21,23 In this study, the simplified PESI outperformed the platelet indices in prognosticating patients with acute PTE.…”
Section: Discussionmentioning
confidence: 93%
“…This can be attributed to the consumption of platelets for thrombus formation and a compensatory production of larger platelets from megakaryocytes in the bone marrow. 22,25 Previous studies have showed a relationship between PLR and a high risk of in-hospital mortality in patients with acute PTE and found it to be correlated with established risk scores (e.g. simplified PESI).…”
Section: Discussionmentioning
confidence: 99%
“…PDW is accepted as a more specific marker of platelet activation because it does not increase in response to platelet swelling. There are some studies in the literature regarding the relationship of PDW with PTE [15,26]. Sevuk et al reported that PDW values were higher in patients who developed acute PTE after DVT than those who did not [27].…”
Section: Discussionmentioning
confidence: 99%